Factores de riesgo asociados a mortalidad en pacientes con sepsis intraabdominal postquirúrgica - Argomedo Alquízar, César Augusto Gabriel (2019)
Postoperative intraabdominal sepsis (SIAP) continues to be a diagnostic and therapeutic challenge for the general surgeon, that despite the advances in surgical treatment, the emergence of intensive care units (ICU) and antimicrobial therapy, continues to present excessively high mortality rates; therefore, it aims to determine which risk factors are associated with mortality in patients with SIAP. Materials and methods: An analytical, observational, retrospective, case-control type study was conducted, based on the review of medical records of patients with SIAP admitted to the ICU of the Regional Hospital of Trujillo, obtaining a total of 141 patients (47 cases and 94 controls). The Chi square nonparametric test was used and the risk was quantified through the Odds Ratio (OR). Results: The variables that constituted risk factors associated with mortality were: gastroduodenal origin of the infection (OR = 8.7; p = 0.0232), preoperative anemia (OR = 39.4; p = 0.000), duration> 2h of surgery (OR = 20.3; p = 0.000), abdominal closure with Bogotá Stock Exchange (OR = 2.48; p = 0.0137), multiple surgical reinterventions (OR = 7.39; p = 0.000), prolonged stay in ICU (OR = 4.73; p = 0.000) and multiple organic failure (OR = 43.7; p = 0.000). Conclusion: Preoperative anemia, duration > 2 h of surgery, abdominal closure with a Bogota bag, gastroduodenal origin of the infection, multiple surgical reinterventions, prolonged stay in the ICU and multiple organ failure, constitute significant risk factors associated with mortality in patients with SIAP.